Built environment, physical activity, and obesity of adults in Pingshan District, Shenzhen City in Southern China. (2nd January 2021) - Dun, Qianqian; Duan, Yiting; Fu, Maozhen; Meng, Hongdao; Xu, Wanglin; Yu, Ting; Debra, Dobbs; Tu, Naidan; Li, Xin; Ma, Lu; Du, Yating; Chen, Longwei; et al.
Abstract: Background: The relation between neighbourhood built environment and obesity has been described as both nuanced and complex. Aim: The objective of this study was to examine the relationship between the built environment, physical activity, and obesity in a rapidly urbanised area of China. Subjects and methods: This is a cross-sectional study. Descriptive statistics were used to describe the socio-demographic variables, physical activity levels and BMI status. Multivariable logistic regression models were used to examine the association between neighbourhood environment, the likelihood of engaging in different types of physical activity, and BMI. Results: A total of 842 respondents completed the questionnaires and were included (84.1% response rate). Among them, 56.4% reported meeting high physical activity levels, while 40.7% were overweight or obese. Multivariable regression analysis showed that better road conditions (β = 0.122, t = 2.999, p = 0.003) and access to physical activity facilities (β = 0.121, t = 3.193, p = 0.001) were significantly associated with higher levels of physical activity. Physical activity levels were inversely associated with the likelihood of being overweight (OR = 0.565, 95%CI: 0.3 4 9–0.917) or obese (OR = 0.614, 95%CI: 0.3 9 0–0.966). Conclusion: The built environment has an important impact on physical activity. However, the direct impact of leisure physical activity on BMI is not significant. This research provides a summary of recent evidence in Pingshan District on built environments that are most favourable for physical activity and obesity.